ANALISIS PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP VARIASI HARGA SAHAM SYARIAH - Esy Nur Aisyah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
Stock price traded on the exchange is closely related to the achievements of the company. Achievementsof the company can be judged from the magnitude of the financial performance during a certain period. Thefinancial performance of the company can be observed from the financial statements issued periodically.Therefore, this study aims to examine the determinants of stock prices in the Indonesian sharia (JII) over aperiod of three years from 2011 to 2013. The results of the regression analysis of the six independent variablesassociated with the use of data from shares sharia (JII) listed on the Stock Exchange. Adjusted R-square value(0.88) indicates that the stock prices of sharia almost 88% depending on the independent variables are EVA,EPS, DPS, ROE, PER and DER, which is owned by the company. Significance Tests showed that EPS and PERis an important determinant of stock prices in the Indonesian sharia. On the other hand, the research also foundthat the explanatory variable is not an explanatory variable explanatory variables EVA, DER, DPS, and ROE isnot strong explanatory variables to determine the price of shares of sharia in Indonesia.